PKM Peningkatan Skala Produksi Sentra Batu Bata Desa Pliken Melalui Peningkatan Kualitas Batu Bata dan Perbaikan Manajemen Usaha - Ratih Windu Arini; I Anna Tul Munikhah; Annisa Utami (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2023)
This community engagement initiative focuses on the production scale of the Brick Center in Pliken Village, Banyumas Regency. The partners are the Brick Artisans Group facing challenges such as low production capacity, products not meeting SNI standards, family-based operations, lack of professional management understanding, limited marketing knowledge, and limited access to loan funds. Proposed solutions include business management mentoring to enhance product quality and artisans' capabilities. Increasing production capacity and implementing a brick stock calculation system are planned. Efforts also encompass capital management training and simulating bank credit proposal drafting. It's expected that these solutions will enable the artisans to overcome challenges, improve product quality, and expand their market reach. In the long term, it's anticipated to contribute to local economic growth. Collaborative efforts between researchers and partners will lead to increased production scale and business quality, providing a positive impact for the entire community of Pliken Village.